2019
DOI: 10.1097/olq.0000000000000984
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mycoplasma genitalium and Association With Human Immunodeficiency Virus Infection in Symptomatic Patients, Johannesburg, South Africa, 2007–2014

Abstract: The human immunodeficiency virus seroprevalence in Mycoplasma genitalium –infected females was significantly higher than in uninfected females, regardless of the presence or absence of other sexually transmitted infection pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
16
2
2
Order By: Relevance
“…The prevalence of MG among pregnant women living with and without HIV in our study is higher than that reported for non-pregnant women living with and without HIV in Johannesburg, South Africa, as well as for that estimated for women in the general population by Baumann et al 6 23. However, the incidence of MG in our study is lower than that reported by three studies in sub-Saharan Africa, which ranged from 6.6 to 34.6 incident MG infections per 100 person-years 24–26.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The prevalence of MG among pregnant women living with and without HIV in our study is higher than that reported for non-pregnant women living with and without HIV in Johannesburg, South Africa, as well as for that estimated for women in the general population by Baumann et al 6 23. However, the incidence of MG in our study is lower than that reported by three studies in sub-Saharan Africa, which ranged from 6.6 to 34.6 incident MG infections per 100 person-years 24–26.…”
Section: Discussioncontrasting
confidence: 77%
“…MG is now a recognised cause of NGU in men and is associated with cervicitis and pelvic inflammatory disease in women 5. In South Africa, a study of men and women living with and without HIV presenting with male urethral syndrome and vaginal discharge syndrome found that MG prevalence was 8.9% and 10.6%, respectively, and another found that prevalence was inversely correlated with age in women 6 7…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have proposed that M. hominis is potentially pathogenic and sometimes associated with a variety of disorders including bacterial vaginosis, pyelonephritis, pelvic inflammatory disease, chorioamnionitis, endometritis, preterm birth, low birth, spontaneous abortion, stillbirth, premature birth, postpartum fever, perinatal mortality and infertility overtime [65,66] [70]. Mahlangu (2019) was determined M. genitalium in 8.9% of urine and 10.6% of endocervical swab specimens which collected from males and females with genital discharge syndrome [71]. Baumann (2017) performed a meta-analysis on prevalence of M. genitalium and found that: the prevalence among women is similar to men and was 1.4% in developed countries and 3.9% in developing countries among general population.…”
Section: Discussionmentioning
confidence: 99%
“…Among asymptomatic men who have sex with men (MSM), M. genitalium appears to be detected significantly more often in the rectum than in the urethra 4 , 15 18 . At the urethral site, M. genitalium is an established cause of NGU and chronic NGU 1 .…”
Section: Contribution Of M Genitalium To Rectal Amentioning
confidence: 99%
“…However, its pathogenicity at other sites, including the rectum, remains subject to debate. Although the prevalence of M. genitalium infection is reported to be higher among persons living with HIV (PLHIV) than in the general population 4 6 , the interplay of M. genitalium –HIV co-infection is poorly understood. Anti-microbial resistance, including the emergence of multi-drug-resistant strains, is complicating current treatment strategies and there is a clear need for use of resistance assays and new classes of anti-microbials.…”
Section: Introductionmentioning
confidence: 99%